2019
DOI: 10.7717/peerj.7941
|View full text |Cite
|
Sign up to set email alerts
|

MHC class I allele diversity in cynomolgus macaques of Vietnamese origin

Abstract: Cynomolgus macaques (Macaca fascicularis, Mafa) have been used as important experimental animal models for carrying out biomedical researches. The results of biomedical experiments strongly depend on the immunogenetic background of animals, especially on the diversity of major histocompatibility complex (MHC) alleles. However, there is much less information available on the polymorphism of MHC class I genes in cynomolgus macaques, than is currently available for humans. In this study, we have identified 40 Maf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 69 publications
(96 reference statements)
0
2
0
Order By: Relevance
“…Although there is an evident discrepancy in the variation of MHC class I genes between the two widely used non-human primate animal models, many studies have demonstrated that a few conserved MHC class I genes in both macaque species may have evolved to fulfill important immune functions. These conserved genes may have fine-tuned their sequences in response to environmental pathogens [ 14 , 93 , 99 ]. Our previous studies have confirmed that ancient introgression occurs at the junction of the two species, as extremely high nucleotide sequence similarity was observed between Chinese rhesus macaques and cynomolgus macaques [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although there is an evident discrepancy in the variation of MHC class I genes between the two widely used non-human primate animal models, many studies have demonstrated that a few conserved MHC class I genes in both macaque species may have evolved to fulfill important immune functions. These conserved genes may have fine-tuned their sequences in response to environmental pathogens [ 14 , 93 , 99 ]. Our previous studies have confirmed that ancient introgression occurs at the junction of the two species, as extremely high nucleotide sequence similarity was observed between Chinese rhesus macaques and cynomolgus macaques [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…The MHC can also be used to investigate mate choice (Kamiya et al., 2014; Leclaire et al., 2019). Hundreds of studies have investigated MHC diversity and cover a large range of taxa, including birds (reviewed by O'Connor et al., 2019), mammals (e.g., Castro‐Prieto et al., 2011; Gigliotti et al., 2021; Huang et al., 2019), fish (reviewed by Yamaguchi & Dijkstra, 2019) and reptiles (e.g., Pearson et al., 2017). Generally, higher MHC diversity enables a population to present a more diverse range of antigens, and hence, on an individual level, is related to higher fitness (Worley et al., 2010) and higher mating success (Kamiya et al., 2014).…”
Section: Introductionmentioning
confidence: 99%